تطبيق مادة الإملاء لترقية مهارة الكتابة في الفصل الوسطى المدرسة الدينية بمعهد دارالفلاح الخامس جومبانج - Mustika Fattahani; Isniayatun Niswah (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2025)
At the Dar Al-Falah V Institute in Jombang, Arabic is taught only once a week, specifically on Saturday night for the first level of the Intermediate Religious class. If the learning takes place only once a week without any additional study hours, then the utilization of this subject is still not optimal. However, if the students are serious about learning Arabic, they will succeed in mastering the Arabic language and writing. In addition to that, the teacher must also have motivation or provide encouragement so that the students remain persistent. Motivation and providing understanding are essential for learning to write in Arabic, because this subject truly requires the teacher’s skill in classroom management. This study explores the implementation of the dictation method as a strategy to enhance students’ writing skills in Arabic. The process integrates multiple instructional components, including reading, writing, and question-and-answer techniques. The dictation activity is conducted in stages. Initially, students copy text intermittently from books or the board. In the next stage, students write from memory after the source is removed. Finally, they engage in blind dictation, writing down what is read aloud without visual aid or spelling assistance. This method aims to assess students’ listening comprehension, retention, and ability to spell Arabic words correctly. The primary goal is not only to test students’ capabilities and perseverance but also to provide targeted support that enables them to overcome difficulties and improve their writing accuracy. This study investigates the implementation of the dictation method as a strategy to improve students’ Arabic writing skills at the Dar Al-Falah V Institute in Jombang. The dictation process is carried out through an integration of various instructional components, including reading, writing, and question-and-answer techniques. The stages of dictation begin with students copying segments of text from a book or the board. In the next phase, students are asked to write from memory after the source material is removed. The final stage involves blind dictation, in which students write down what is dictated to them without any visual reference or spelling assistance. This approach emphasizes listening and spelling accuracy, aiming to test students’ comprehension, memory, and perseverance. Importantly, the purpose of this method is not only to assess students’ capabilities but also to provide them with the necessary support to overcome difficulties and improve their writing accuracy in Arabic.